(untitled) (Revista Argentina de Musicología, 2018)
From the Substitution to the Transposition After the military uprising of June 4th, 1943, the new authorities decided to systematically and severely apply the legislation which, since 1933, had been regulating radio broadcasts. Its aim was to purify the language, protect “good taste” and transmit certain moral values. Hereby begins a new phase of radial censorship that would last six years, and in which the tango lyrics were one of the main targets of the controlling system. Most of the modifications were made by the songwriters themselves. In some cases, it was a simple lexical substitution. In other cases, rime or metrics imposed certain restrictions that generated very different style variants. There were also tangos where the censorship maneuver was aimed at moderating passion and masking certain edges of the story told, or even transforming its political content into something else. Perhaps the most extreme examples, in terms of the modifications made to satisfy the censors, are two tangos of Celedonio Flores –Mano a mano and El bulín de la calle Ayacucho– whose new versions exhibit a rewriting process that may be defined and analyzed by what Gerard Genette calls transposition.